Integrative analysis identifies potential ferroptosis-related genes of hypoxia adaptation in yak - Zhang, Jian; Cui, Yan (Frontiers in Veterinary Science, 2022)
There are studies on the hypoxia adaptation in yak, but there are few studies on the regulation of ferroptosis by hypoxia. This study was the first time to explore ferroptosis-related genes about hypoxia in yak. In this study, the oviduct epithelial cells between yak and bovine are performed by integrative analysis for functions, regulating network and hub genes. The results showed 29 up-regulated ferroptosis genes and 67 down-regulated ferroptosis genes, and GO-KEGG analysis showed that up-regulated differentially expressed genes (DEGs) were significantly enriched in ribosome pathway and oxidative phosphorylation pathway. Down-regulated DEGs were significantly enriched in longevity regulating pathway-mammal pathway. Mitophagy-Animal Pathway was a significant enrichment pathway for the up-regulated differentially expressed ferroptosis genes (DE-FRGs). HIF-1 signaling pathway is a significant pathway for the down-regulated DE-FRGs. By constructing DE-FRGs protein-protein interaction (PPI) network, 10 hub DE-FRGs (Jun, STAT3, SP1, HIF1A, Mapk1, Mapk3, Rela, Ulk1, CDKN1A, EPAS1) were obtained. The bta-mir-21-5p, bta-mir-10a and bta-mir-17-5p related to STAT3 were predicted. The results of this study indicated the important genes and pathways of the hypoxia in yak, and it was the first time to study ferroptosis genes and pathways related to the hypoxia adaptation by bulk-seq in yak. This study provided sufficient transcriptome datas for hypoxia adaptation.